Pengaruh Penerapan Strategi Metakognitif pada Masa Pandemi terhadap Hasil Belajar Siswa Kelas XI IPS di SMA Negeri 8 Ambon - Amram Alfred Halono; Aminah Rehalat; Silvia Manuhuttu (Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of metacognitive strategies on the learning outcomes of Grade XI Social Studies students in Economics at SMA Negeri 8 Ambon during the pandemic. Metacognitive strategies were selected for their ability to help students recognize, control, and evaluate their own thinking processes—an essential skill in remote learning environments that require high autonomy. The research used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The sample included two classes: an experimental group using metacognitive strategies and a control group employing conventional methods. Instruments included a multiple-choice learning outcomes test and an observation sheet for student learning activities. The results show that the application of metacognitive strategies significantly improves students' learning outcomes. It also enhances student engagement, reflective thinking, and decision-making in solving economics problems. The study recommends that teachers incorporate more metacognitive strategies into the teaching process, especially in online or hybrid learning settings